# simplify this equation?

2a+3b+6a-7b

please simplify this for me and explain how you did it

• Puzzling
1 month ago

Get your a and b terms grouped together:

(2a + 6a) + (3b – 7b)

Now simplify:

(2 + 6)a + (3 – 7)b

= 8a – 4b

• akoni
1 month ago

Simplify means to remove parentheses () and put like terms together.

Since there are no parenthesis given, we simply combine like terms.

2a and 6a are like terms since they have the same literal coefficient, “a”.

3b and -7b are also like terms, with the same literal coefficient, “b”.

Combining both sets of like terms results in:

2a+6a = 8a

3b-7b = -4b

Therefore, the simplified form is:

8a-4b

Going further by find a common factor of the two terms such that it becomes

4(2a-b)

is no longer “simplifying” but “factoring”.

• ?
1 month ago

Question= 2a+3b+6a-7b

Solution=(2a+6a)+(3b-7b)

={(2+6)a}+{(3-7)b}

=8a+(-4)b

=8a-4b (Ans)

• Moon
1 month ago

2a+3b+6a-7b => 2a+6a+3b-7b =>(2+6)a + (3-7)b => 8a -4b

• Eric
1 month ago

2a + 3b + 6a – 7b

= 2a + 6a + 3b – 7b . . . <= do the sum for like terms

= 8a – 4b

Done

• Anonymous
1 month ago

just do 2a + 6a = 8a

then 3b – 7b = -4b

which then = 8a – 4b

• Watev
1 month ago

2a+6a = 8a.

3b-7b = -4b

So simplified is 8a-4b.

Just combine like terms.

• Como
1 month ago

8 a – 4 b

• Anonymous
1 month ago

2a+3b+6a-7b

2a + 6a = 8a

3b – 7b = -4b

so it is 8a – 4b =]

• Anonymous
5 days ago

2b – b + 8 + 2 = b + 10